2008
DOI: 10.1080/09720529.2008.10698204
|View full text |Cite
|
Sign up to set email alerts
|

Extension of line-splitting operation from graphs to binary matroids

Abstract: In this paper, we characterize the n-line splitting operation of graphs in terms of cycles of respective graphs and then extend this operation to binary matroids.In matroids, we call this operation as element-set splitting. For convenience, we call the resulting matroid, es-splitting matroid. We characterize circuits of es-splitting matroid. We also characterize the es-splitting matroid in terms of matrices.We also show that if M is a connected binary matroid then es-splitting matroid M e X is also connected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…For r ! 3, let A r be the r  ð2r þ 1Þ matrix ½I r jJ r À I r j1 over GF (2) whose columns are labeled, in order, x 1 , x 2 , :::, x r , y 1 , y 2 :::, y r , t: The vector matroid M½A r of this matrix is called the rank-r binary spike with tip t and denoted by Z r . Oxley [4] showed that all rank-r, 3-connected binary matroids without a 4-wheel minor can be obtained from a binary r-spike by deleting at most two elements.…”
Section: Proposition 2 [3]mentioning
confidence: 99%
See 4 more Smart Citations
“…For r ! 3, let A r be the r  ð2r þ 1Þ matrix ½I r jJ r À I r j1 over GF (2) whose columns are labeled, in order, x 1 , x 2 , :::, x r , y 1 , y 2 :::, y r , t: The vector matroid M½A r of this matrix is called the rank-r binary spike with tip t and denoted by Z r . Oxley [4] showed that all rank-r, 3-connected binary matroids without a 4-wheel minor can be obtained from a binary r-spike by deleting at most two elements.…”
Section: Proposition 2 [3]mentioning
confidence: 99%
“…In this section, our main goal is to give a necessary and sufficient condition for X EðZ r Þ with e 2 X, to obtain Z rþ1 by applying the es-splitting operation on X. Now suppose that M ¼ Z r be a binary rank-r spike with the matrix representation ½I r jJ r À I r j1 over GF (2) whose columns are labeled, in order x 1 , x 2 , :::, x r , y 1 , y 2 , :::, y r , t:…”
Section: Theorem 4 [4]mentioning
confidence: 99%
See 3 more Smart Citations